Influence of Krakow winter and summer dusts on the redox cycling of vitamin B12a in the presence of ascorbic acid - Polaczek, Justyna; Jodłowska, Angelika; Stochel, Grażyna; Van Eldik, Rudi (Atmosphere, 2021)
Air pollution remains a serious problem in Krakow, Poland. According to the European Environmental Agency, annual mean levels of both PM2.5 and PM10 recorded in Krakow are much higher than EU limit values. Thus, the influence of particulate matter (PM) on the function of living organisms, as well as different physiological processes, is an urgent subject to be studied. The reported research forms part of the multi-disciplinary project ‘Air Pollution versus Autoimmunity: Role of multiphase aqueous Inorganic Chemistry,’ which aims to demonstrate the PM effect on the immune system. The present studies focused on the role of dust collected in Krakow on the redox cycling of vitamin B12a in the presence of ascorbic acid. Dust samples collected during the winter 2019/2020 and summer 2020 months in the city center of Krakow were characterized using various analytical techniques. The influence of Krakow dusts on the kinetics of the reaction between nitrocobalamin and ascorbic acid was confirmed and discussed in terms of the composition of the samples. Possible reasons for the reported findings are provided.
CRIS-Team Scopus Importer:2021-08-27
Keywords: Air pollution; Ascorbic acid; Nanoparticles; Nitrocobalamin; Nitrosylcobalamin; Particulate matter; Redox reactions